2001
DOI: 10.3758/bf03196201
|View full text |Cite
|
Sign up to set email alerts
|

Directing attention to movement effects enhances learning: A review

Abstract: Studies investigating the influence of the learner' s focus of attention, induced by instructions or feedback, on motor skill learning are reviewed. In general, directing performers' attention to the effects of their movements (external focus of attention) appears to be more beneficial than directing their attention to their own movements (internal focus of attention). Preliminary evidence is presented indicating that an internal attentional focus constrains the motor system by interfering with natural control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
393
4
25

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 577 publications
(457 citation statements)
references
References 70 publications
35
393
4
25
Order By: Relevance
“…Drawing on Wulf and Prince's [33] research regarding the focus of attention (where an external focus is regarded as better for performance than an internal focus), we hypothesize that performance goals may influence strength performance more positively than process goals. Performance goals may be aligned with an external focus, whereas process goals may be associated with an internal focus.…”
Section: Discussionmentioning
confidence: 99%
“…Drawing on Wulf and Prince's [33] research regarding the focus of attention (where an external focus is regarded as better for performance than an internal focus), we hypothesize that performance goals may influence strength performance more positively than process goals. Performance goals may be aligned with an external focus, whereas process goals may be associated with an internal focus.…”
Section: Discussionmentioning
confidence: 99%
“…One speculative possibility is that gaming may involve aspects of automatic processing. Such an interpretation would be consistent with findings from sports studies in which automatic processing may be accompanied by improved performance, with extra attention potentially disrupting optimal performance (Wu et al., 2015; Wulf & Prinz, 2001). Studies have also suggested that during a competitive task, more attention to performance, leading to less automaticity, may disrupt a well‐practiced skill (Wulf & Prinz, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Such an interpretation would be consistent with findings from sports studies in which automatic processing may be accompanied by improved performance, with extra attention potentially disrupting optimal performance (Wu et al., 2015; Wulf & Prinz, 2001). Studies have also suggested that during a competitive task, more attention to performance, leading to less automaticity, may disrupt a well‐practiced skill (Wulf & Prinz, 2001). Other findings suggest that when a movement becomes automatic, neural efficiency is increased by the strengthening of connections within specific neural networks (Balsters & Ramnani, 2011; Wu et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations